Dynapenic abdominal obesity as predictor of mortality and disability worsening in older adults: A 10-year prospective study. Issue 1 (February 2016) - Rossi, Andrea P.; Fantin, Francesco; Caliari, Cesare; Zoico, Elena; Mazzali, Gloria; Zanardo, Marina; Bertassello, Paolo; Zanandrea, Valeria; Micciolo, Rocco; Zamboni, Mauro
Summary: There are relatively few prospective studies evaluating the combined effect of abdominal obesity and low muscle strength on worsening disability and on mortality. The study aimed at evaluating prospectively the prognostic value of dynapenic abdominal obesity definition on disability worsening in a 5.5-year follow-up and mortality in a 10-year follow-up. Methods: In 93 men and 169 women aged between 66 and 78 years, leg isometric strength, waist circumference (WC), BMI, glycemia, HOMA, lipid profile, vitamin D3, albumin, fibrinogen, physical activity level, income, smoking status and comorbidities were evaluated at the baseline. Reported disabilities were measured at baseline, 1-y, 2-y, 3-y and 5.5-y follow-up and mortality rate was evaluated during a 10-y follow-up. The study population was categorized in dynapenic abdominal obese (D/AO), nondynapenic abdominal obese (ND/AO), dynapenic nonabdominal obese (D/NAO), nondynapenic nonabdominal obese (ND/NAO) according to muscle strength/WC tertiles. Results: D/NAO subjects presented a disability worsening risk of 1.69 times (95%CI:1.11–2.57), ND/AO subjects showed a 2-fold increase in risk (95%CI:1.34–2.98), while being D/AO more than trebled the risk, even after considering confounding variables (HR:3.39, 95%CI:1.91–6.02). Mortality risk after adjustment for other confounding variables was 1.57 (95%CI:1.16–2.13) for ND/AO and 2.46 (95%CI:1.34–4.52) for D/AO. Conclusions: Dynapenic abdominal obese subjects are at higher risk of worsening disability and mortality than subjects with dynapenia or central fat distribution only.